Komunikasi Suami Istri Dalam Meningkatkan Kesejahteraan Pernikahan - Azzahra, Bening Surya; Salmi, Hamidatul; Qalbi, Hidayatul; Citra, Neli Julia; Vatin, Nurva Dillatul (Affection: Journal of Psychology And Counseling, 2024)
Communication between husband and wife is important in a marriage because with close communication between husband and wife, prosperity can be achieved in marriage. A husband who will act as a father, and a wife who will act as a mother will also strive to achieve prosperity in their family. However, to achieve prosperity, effective communication between husband and wife is needed. The aim of this research is to explore previous research related to the theme of Communication in Marriage. This research uses a scoping approach review. Search and collection of literature sourced from Google pages scholar based on publications from the last seven years (2018-2024). Literature is selected using a flow diagram. The results of this research are narrowing previous literature into 4 pieces of literature for review. The discussion in the literature is related to the importance of communication between husband and wife to achieve marital and family prosperity.